TURKEY’S SEARCH FOR SECURITY AND THE SOVIET FACTOR DURİNG THE SECOND WORLD W AR - Şaban Çalış (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
In this essay, an attempt has been inade to analyse Turkey’s search for security during the Second World War within the context of the Soviet factor and Turkish diplomatic relations with the great powers. It has taken the establishment of the Tripartite Agreement of 1939 as a starting point and tried to provide an analysis of events leading to Ankara’s decision of declaring war on the Axis in 1945. By doing this, the reasons why Turkey did not enter the War until the eleventh hour have been examined thoroughly and the author came to conclusion that there is a strong correlation between Ankara’s search of security, the Soviet factor and the policies of the Allied povvers against Turkey. Therefore, the author suggests that in addition to many other factors, this correlation needs to be established in order to understand Turkish foreign policy properly during the Second World War.